2005
DOI: 10.1038/sj.ejcn.1602275
|View full text |Cite
|
Sign up to set email alerts
|

Folate and vitamin B12 in relation to lactation: a 9-month postpartum follow-up study

Abstract: Objective: To investigate the relation between lactation and markers of folate and vitamin B12 (B12) deficiency in women with and without vitamin supplementation. Design: A 9-month follow-up study. Subjects and methods: Blood samples from 91 women, who gave birth to a single healthy child, were collected 3 weeks, 4 and 9 months postpartum and analysed for circulating level of homocysteine (tHcy), methylmalonic acid (MMA), folate and B12. The participants were categorized as exclusively, partly or not breast-fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…The serum folate was not higher in the formula-fed infants (19). The association between lactation and folate status was observed (20). From this study the results of RBC folate concentration levels were similar in the fi rst two months of life in comparison with our previous fi ndings related to Slovakian newborns (21).…”
Section: Discussionsupporting
confidence: 43%
“…The serum folate was not higher in the formula-fed infants (19). The association between lactation and folate status was observed (20). From this study the results of RBC folate concentration levels were similar in the fi rst two months of life in comparison with our previous fi ndings related to Slovakian newborns (21).…”
Section: Discussionsupporting
confidence: 43%
“…It has been suggested that folate status of the lactating mother in these study populations often declines merely due to the discontinuation of prenatal folic acid supplements [154]. A number of studies have been carried out on maintenance of blood folate status during lactation [76,152,155,156,157]; however, these studies have also been conducted in groups of women who had consumed high-dose folic acid supplements throughout pregnancy.…”
Section: Nutrient Intake Values For Folate In Use Around the Worldmentioning
confidence: 99%
“…Infantile vitamin B-12 deficiency can lead to neurologic impairments including irritability, apathy, and developmental regression (16)(17)(18). Although a few studies have examined longitudinal changes in maternal vitamin B-12 biomarkers during lactation (14,(19)(20)(21), less is known about the impact of this reproductive state (compared to the nonlactating state) on vitamin B-12 status and requirement.…”
Section: Introductionmentioning
confidence: 98%